Facilitated Tenon-Free Conjunctival Autograft Preparation and Limited Tenon Removal Technique in Pterygium Surgery - Ucar, Fikret; Seyrek, Lutfi; Cetinkaya, Servet; Ture, Huseyin; Kadioglu, Ekrem (Klinische Monatsblätter für Augenheilkunde, 2021)
Background The main complication of primary pterygium surgery is the recurrence of the pterygium. In the present study, we aimed to compare a classical technique and facilitated tenon-free conjunctival autograft preparation and a limited tenon removal technique in pterygium surgery in terms of recurrence rate, complications, and operation duration.Material and Methods This is a retrospective, comparative, observational study. Group 1 comprised 120 eyes of 115 patients who underwent pterygium excision with a new facilitated tenon-free conjunctival-limbal autograft preparation and limited tenon removal technique between May 2017 and October 2019. Group 2 comprised 117 eyes of 113 patients who underwent pterygium excision with a conventional conjunctival-limbal autograft technique between January 2016 and May 2017.Results The mean follow-up time after surgery was 18.2 ± 5.8 months in group 1 and 19.1 ± 6.3 months in group 2 (p = 0.25). The mean operation duration was 5.54 ± 1.22 (4 – 7) minutes in group 1 and 8.23 ± 1.26 (8 – 10) minutes in group 2 (p = 0.02). Flap edema was present in 33 eyes (28.2%) in group 2 and in 11 eyes (9.16%) in group 1. Flap edema was significantly higher in group 2 (p < 0.001). At the end of the 1-year follow-up of the patients, we observed recurrence in only one (0.83%) eye in group 1 and 14 (11.96%) eyes in group 2. The recurrence rate of group 1 was significantly less than that of group 2 (p < 0.001).Conclusions The simplified technique of tenon-free conjunctival autograft preparation and limited tenon removal yielded better clinical outcomes without serious complications. Additionally, this technique shortened the surgical time and reduced surgeon-dependent factors.
Keywords: pterygium surgery; recurrence; tenon-free conjunctival autograft; limited tenon removal